Exploration of the Challenges of COVID-19 from the Perspective of Emergency Medicine Specialists - Tayebeh Rakhshani; Farzaneh Ghalehgolab; Mohammad Amin Bahrami; Shahnaz Karimi; Hadid Hamrah; Fatemeh Jafari; Ali Khani Jeihooni (Emergency Medicine International)
Background. Emergency physicians are at the forefront of the medical system in the face of the COVID-19 crisis. Identifying the challenges, along with the strategies and effective measures implemented by them in the face of the COVID-19 crisis, can be a roadmap for future crisis management planning. This study aims to explain the challenges faced by emergency physicians regarding COVID-19. Methods. This study is a qualitative content analysis. Data were collected using individual and semistructured interviews. Twenty-seven emergency medical specialists in Fars University of Medical Sciences, Iran, participated in the study by purposive sampling method and were interviewed using semistructured interviews. Results. Participants’ experience of COVID-19 led to the extraction of four main themes, including structural factors, threats to the health of the medical team, fluctuations of extremism and wastage in the face of COVID-19, and the country’s policymaking hierarchy. Conclusions. Emergency physicians face challenges such as structural factors, health threats, extreme fluctuations, and national policymaking. To avoid surprises and threats, they must predict acute scenarios, provide necessary equipment, address skilled manpower shortages, and adopt appropriate management policies. This includes culture-building, cross-sector coordination, planning, and efficient management to prevent virus spread.